2020
DOI: 10.1002/chem.202003431
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Enabled C−H Functionalization by a Direct Hydrogen Atom Transfer Uranyl Photocatalyst

Abstract: The development of the uranyl cation as ap owerful photocatalyst is seriously delayed in comparison with the advances in its fundamental and structuralc hemistry.H owever,i ts characteristich igh oxidative capability in the excited state ([UO 2 ] 2 + *(+ 2.6 Vv s. SHE;S HE = standard hydrogen electrode) combined with blue-light absorption (hv = 380-500 nm) and al ong-livedf luorescencel ifetime up to microseconds have reveals that the uranylc ation approaches an ideal photocatalyst for visible-light-driven org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 98 publications
0
28
0
Order By: Relevance
“…Compared with the above thermal reaction process using of expensive metals as the catalysts or under harsh reaction conditions, the visible‐light driven hydrogen atom transfer of the aldehyde for acyl‐radical generation allows a convenient and mild reaction condition for the organic transformation [8,9] . Wang and co‐workers reported an α,β‐epoxy ketones generation approach under visible light photochemical conditions, and the β‐peroxyketones as the intermediates [10] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the above thermal reaction process using of expensive metals as the catalysts or under harsh reaction conditions, the visible‐light driven hydrogen atom transfer of the aldehyde for acyl‐radical generation allows a convenient and mild reaction condition for the organic transformation [8,9] . Wang and co‐workers reported an α,β‐epoxy ketones generation approach under visible light photochemical conditions, and the β‐peroxyketones as the intermediates [10] …”
Section: Methodsmentioning
confidence: 99%
“…[7] Compared with the above thermal reaction process using of expensive metals as the catalysts or under harsh reaction conditions, the visible-light driven hydrogen atom transfer of the aldehyde for acyl-radical generation allows a convenient and mild reaction condition for the organic transformation. [8,9] Wang and co-workers reported an α,β-epoxy ketones generation approach under visible light photochemical conditions, and the β-peroxyketones as the intermediates. [10] Regards to indole derivatives have the unique property of mimicking the structure of peptides and enzymes, which provide tremendous opportunities to discover novel drugs with different modes of action, [2b] we herein report an example of three-component acylation/peroxidation reactions by the visible-light photocatalysis (Scheme 1).…”
mentioning
confidence: 99%
“…Decatungstates such as tetrabutylammonium decatungstate, ( n‐ Bu 4 N) 4 W 10 O 32 (TBADT) and sodium decatungstate, Na 4 W 10 O 32 (NaDT) have been shown to have interesting photophysical properties and photochemical activity towards C−H functionalization [40–50] . In 2018, MacMillan et al.…”
Section: Dual Photocatalyzed Hat and Nickel Catalysismentioning
confidence: 99%
“…Decatungstates such as tetrabutylammonium decatungstate, (n-Bu 4 N) 4 W 10 O 32 (TBADT) and sodium decatungstate, Na 4 W 10 O 32 (NaDT) have been shown to have interesting photophysical properties and photochemical activity towards CÀ H functionalization. [40][41][42][43][44][45][46][47][48][49][50] In 2018, MacMillan et al demonstrated that the merger of TBADT-based HAT catalysis with nickel catalysis could achieve the photochemical (hetero)arylation of cycloalkanes and other strong C(sp 3 )À H precursors with (hetero) aryl bromides (Scheme 4a). [51] A wide variety of C(sp 3 )À C(sp 2 ) cross-coupled products including functionalized drug-like molecules were obtained in satisfactory yields in this way.…”
Section: Dual Photocatalyzed Hat and Nickel Catalysismentioning
confidence: 99%
“…Subsequently, detailed mechanistic studies were carried out by Shi and co-workers. 31 Radical trapping experiments demonstrated that the conversion was completely suppressed in the presence of 2,2,6,6-tetramethylpiperidine-1oxyl (TEMPO) under standard conditions, and that the radical adduct of THF-TEMPO was detected in significant quantities by ESI-MS analysis, which means the THF radical was involved as an intermediate in this transformation. In addition, U V -oxo radical character was detected by EPR experiments, which revealed that the THF radical was generated by *UO 2 2+ via hydrogen-atom transfer, and the course as the rate-determining step.…”
Section: Scheme 14 Construction Of Phenol Derivativesmentioning
confidence: 99%